Micronodular Thymoma with Lymphoid Stroma: A Mediastinal Mass Masquerading as a Pericardial Mass - Kent Swimley; Hilda M. Gonzalez-Bonilla; Alpana Senapati; Karla M. Kurrelmeyer (Methodist DeBakey Cardiovascular Journal)
A 61-year-old man presented to the emergency room with lower extremity edema. Physical exam was only remarkable for a diastolic murmur in the right carotid area and left lower extremity edema. Venous Doppler revealed a deep venous thrombosis in the left lower extremity. Chest computed tomography (CT) with intravenous contrast ruled out pulmonary embolism but showed a mediastinal mass adjacent to the pericardium. Further imaging with cardiac magnetic resonance imaging (CMR) and cardiac CT angiography (CCTA) enabled localization and evaluation of the structural characteristics of the mass. The decision was made to excise the mass due to increasing size compared with its measurements on prior chest CTs and a high degree of vascularization seen on CMR and CCTA, which was concerning for an enlarging arteriovenous malformation or a hemangioma. However, histopathologic analysis of the mass revealed it to be a micronodular thymoma.